(cosecA - sin A)/(cosec A + sin A) = (sec^2 A - tan^2 A)/(sec^2 A + tan^2 A)
step by step explanation
Answers
Answered by
34
reffer to the attachment
hope it helps you
Attachments:
![](https://hi-static.z-dn.net/files/deb/67ee52236ce2eb4f931048720df29757.jpg)
Answered by
1
L.H.S. = (cosec A – sin A)(sec A – cos A). sec2 A
= (1/sin A – sin A). (1/cos A – cos A). 1/cos2 A
= (1 – sin2 A/sin A) × (1 – cos2 A/cos A) × 1/cos2 a
= cos2 A/sin A × sin2 A/cos A × 1/cos2 A
[∵ (1 – sin2 A) = cos2 A]
[∵ 1 – cos2 A = sin2 A]
= sin A/cos A = tan A
= R.H.S.
Hence proved.
Similar questions